The Effect of Heyzine Flipbook Project-Based Learning on Students’ Academic Independence - Firdiawan Ekaputra (JUPE : Jurnal Pendidikan Mandala, 2026)
This study aims to determine the effect of Heyzine Flipbook Project-Based Learning on students’ learning autonomy in the Educational Multimedia Design course in the Chemistry Education Program at the Universitas Jambi. This study employs a quantitative approach using a pre-experimental method with a One-Group Pretest-Posttest Design. The research subjects are students enrolled in the Educational Multimedia Design course. Data collection was conducted using a learning independence questionnaire administered before and after the intervention. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and a paired-sample t-test. The results of the study show that students’ average level of independent learning increased from 72.14 to 85.50. The paired-sample t-test yielded a p-value of 0.000, indicating that the implementation of Project-Based Learning using the Heyzine Flipbook had a significant effect on students’ independent learning.